2017
DOI: 10.1016/j.apenergy.2016.05.096
|View full text |Cite
|
Sign up to set email alerts
|

Climatic analysis of a passive cooling technology for the built environment in hot countries

Abstract: The aim of this work was to determine the ventilation and cooling potential of a passive cooling windcatcher operating under hot climatic conditions by replicating the monthly wind velocity, wind direction, temperature and relative humidity (RH) observed in a hot-desert city. The city of Ras-Al-Khaimah (RAK), UAE was used as the location of the case-study and available climatic data was used as inlet boundary conditions for the numerical analysis. The study employed the CFD code FLUENT 14.5 with the standard k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(13 citation statements)
references
References 34 publications
(100 reference statements)
0
13
0
Order By: Relevance
“…The study found that the new system can lower the supply air in the range from 10°C to 20°C. Calautit et al [32] undertook a CFD study to see the ventilation and cooling potential in a hot climate in the United Arab Emirates. An experiment was also done and the results of the experiment showed both a positive cooling effect and some issues in the indoor thermal environment for certain periods.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The study found that the new system can lower the supply air in the range from 10°C to 20°C. Calautit et al [32] undertook a CFD study to see the ventilation and cooling potential in a hot climate in the United Arab Emirates. An experiment was also done and the results of the experiment showed both a positive cooling effect and some issues in the indoor thermal environment for certain periods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature review showed that a few studies investigated how the cool humid supply air that a spray PDEC system discharges affect the indoor thermal environment [5,12,[19][20][21]26,28,32]. The majority of the building applications using PDEC technology operated with no performance control, or applied a simple on-off control, rather than immediately responding to the variable cooling loads [5,12,20,22].…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, the effective area sufficient for windows or vents should be determined and the driving force sufficient to move the ventilated air should be designed to ensure design flexibilities at the later stage when the detailed natural ventilation design is performed. Natural ventilation should be implemented considering other passive heating or cooling designs [27] as well as advanced HVAC operations [28]. Even a complex facility integrating daylighting and natural ventilation functions may be installed [29].…”
Section: Introductionmentioning
confidence: 99%
“…The blockage ratio is defined as the cross-sectional area of the tower in the domain area. This parameter must be small enough to avoid the blockage effect, and we determine that the blockage ratio is around 3.3% which is considered acceptable for the simulations [43,44]. …”
Section: Geometrical Modelingmentioning
confidence: 99%
“…Steady-state three-dimensional CFD simulations are performed with a standard k-ε turbulence model, following previous studies on wind towers [1,[43][44][45][46][47][48][49]. It is possible to predict the natural ventilation airflows inside and around wind towers and also indoor airflows with this approach.…”
Section: Solver and Boundary Conditionsmentioning
confidence: 99%